2016
DOI: 10.1007/s00701-016-3027-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of vagal nerve stimulation in medication-resistant epilepsy. Comparison between patients with and without medication changes

Abstract: We did not find a statistical difference in seizure frequency reduction between patients with or without changes in medication during their follow-up, so changes in medication did not improve the outcome. Furthermore, the absence of changes in AED can help to optimize the parameters of the stimulator in order to improve its effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
1
23
0
1
Order By: Relevance
“…We analyzed age at seizure onset within each group in six studies [15,16,[18][19][20]24], including 416 patients; we found no significant difference between the good responders and poor responders (p = 0.530, SMD = 0.075, 95% CI: -0.159 to 0.310, heterogeneity test: Chi 2 = 7.44, p = 0.190, I 2 = 32.8%, Fig. 3).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We analyzed age at seizure onset within each group in six studies [15,16,[18][19][20]24], including 416 patients; we found no significant difference between the good responders and poor responders (p = 0.530, SMD = 0.075, 95% CI: -0.159 to 0.310, heterogeneity test: Chi 2 = 7.44, p = 0.190, I 2 = 32.8%, Fig. 3).…”
Section: Discussionmentioning
confidence: 94%
“…At 6 m, 1, 2, 3, 4, 6 and 12 years after implantation, 33.99, 43.42, 46.50, 63.31, 52.71, 54.64, 70.37 and 82.90% of patients exhibited > 50% reduction of seizure frequency after VNS. In the 14 trials [7,[10][11][12][14][15][16][17][18][19][20][21][22]24], including a total of 906 participants, analysis age at VNS implantation as a predictor for VNS outcome within each group, we found no significant difference between the good responders and poor responders (p = 0.305, SMD = -0.075, 95% CI: -0.220 to 0.069; heterogeneity test: Chi 2 = 12.20, p = 0.526, I 2 = 0%, Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 63% of the patients in drug unchanged group had a 50% frequency of seizure reduction, and 45.2% of the patients within drug change group had the 50% frequency of seizure reduction. Therefore, there is no statistical difference in frequency reduction whether there is any change of drugs . Changing the dosage and type of antiepileptic drugs (AED) may not influence the treatment results of VNS.…”
Section: Applicationmentioning
confidence: 99%
“…Therefore, there is no statistical difference in frequency reduction whether there is any change of drugs. 25 Changing the dosage and type of antiepileptic drugs (AED) may not influence the treatment results of VNS.…”
Section: Appli C Ati Onmentioning
confidence: 99%